Analisis Banjir Rancangan dengan Metode Inversely Estimated Rainfall - Widyasari, Titiek (MEDIA KOMUNIKASI TEKNIK SIPIL, 2008)
To avoid the paucity of rainfall data, development of flood estimation methods that rely on hydrograph data are required. Hydrograph data are the output of the catchment. It means that all the catchment behaviors are represented in the runoff data. The effect of temporal and the spatial variability of rainfall and the initial soil moisture condition has been represented in the runoff data. Hence, it’s necessary research about of design flood used on hydrograph. The research uses 16 flood events collected from Bojongloa sub-river basin and 10 data from Leuwigoong sub-river, which all included Cimanuk river basin in West Java. The filter separation autoregressive method is selected to separate the hydrograph to become baseflow and direct runoff components. The resulted direct runoff is then used for deriving the effective rainfall using inversely estimated rainfall (IER) method. The result of IER rainfall and IER pattern is used in design flood analysis using unit hydrograph IER method. And the observed rainfall are used as comparisons. The result show that design flood with hydrograph IER method is relatively similar with the observed rainfall. The result design flood with hydrograph IER method give accuracy between design flood the result of frequency analysis.Keywords : hydrograph, inversely estimated rainfalls, unit hydrographPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3668[How to cite: Widyasari, T. (2008), Analisis Banjir Rancangan dengan Metode Inversely Estimated Rainfall, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, No. 1, pp. 87-98]